Promoting academic success among Swedish adult students with neuropsychiatric disorders and mental health issues - Ulla Damber; Lena Randevåg (Social Sciences and Humanities Open)
Municipal Adult Education in Sweden has recently undergone changes, from on-site education to outsourced courses by external course providers with large, standardized courses distributed on-line. This educational context has proven difficult to manage for target group of this study, students with neuropsychiatric disorders and mental health issues, with large number of dropouts as a result. The present study aimed to explore how support adapted to the target group was perceived by students included in a project, Right to Support, where teachers on-site functioned as intermediary between the external course providers and target group. Eight students were in-depth interviewed, and their narratives were analyzed with reflexive thematic analysis. The narratives indicated five themes including prerequisites for learning, adapted physical environment, firsthand assistance, personal relationships and effects for self-esteem. We conclude that these factors enabled academic success, personal growth and potential for societal inclusion.